À qui appartient-il de déterminer les modes d’intervention auprès des personnes intersexuées ? - Bastien Charlebois, Janik (Nouvelles pratiques sociales, 2016)
Les personnes intersex(ué)es sont au coeur de tensions dans l’orientation des pratiques médicales sur leur corps et la détermination de leur « propre bien ». La volonté d’autodétermination relayée par les acteurs sociaux politisés et les critiques qu’ils formulent à l’endroit des médecins se heurtent au déficit de crédibilité que celle-ci leur accorde. En isolant certains des motifs les plus solides du maintien de la primauté médicale sur l’orientation des pratiques, nous relevons les arguments développés par la communauté intersexe pour y répondre. Cette réflexion est menée à partir des perspectives philosophiques de Young sur l’autodétermination et du concept d’injustice épistémique de Fricker.
Keywords: approches et analyses; autodétermination; corps; cours; discipline; fem1000; histoire et politique; identités LGBTQIA2+; lit4700; militance; médecine; personnes intersexes; point de vue situé; premier cycle; ressource en ligne; sciences; thématiques

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social